(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2016)
The minimum age for criminal responsibility refers to the age at which children can be reasonably and fairly considered liable for their criminal actions. To date, determination of the minimum age of child criminal responsibility still remains a controversial issue among the justice systems across the world where juveniles are concerned. Current practice in various justice systems reveals that there is no uniformity in setting the minimum age for child criminal responsibility. Reference to international instruments reveals that there are specific principles and guidelines outlined by these instruments on this matter.Thus, this paper will try to examine principles and guidelines set by the international instruments on this matter. In addition, this paper also will attempt to analyze comparatively the extent to which the current Malaysian legal framework in this matter complies with the international legal standards, and highlight possible suggestions for the improvement of existing laws and policies. Keywords: children, criminal responsibility, international laws, minimum age